Policy Analysis of Standard Traders in Sidoarjo District - Risma Pratiwi; Hendra Sukmana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is a literature study on the government policy. This study aims to discuss what efforts can be implemented by street vendors in maintaining their business in the midst of the covid-9 pandemic. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study concluded that PKL Law Enforcement on the Main Street of Taman Pinang Housing, Sidoarjo Regency Law enforcement of street vendors on the Main Street of Taman Pinang Indah Housing was carried out by local SKPD based on applicable regional regulations. These regional regulations include Regional Regulation No. 10 of 2013, Regional Regulation No. 3 of 2016 and the Decree of the Regent of Sidoarjo No. 188/455/404.1.1.3/2017. Obstacles faced by local governments include less intensive policy implementation, less strategic relocation solutions, pressure groups, illegal street vendors who do not want to be relocated, budget constraints.